2019
DOI: 10.18781/r.mex.fit.1911-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and characterization of antagonistic rhizobacteria to Sclerotium cepivorum

Abstract: La pudrición blanca causada por el hongo <em>Sclerotium cepivorum</em> ocasiona grandes pérdidas económicas en el género <em>Allium</em> a nivel nacional. En este trabajo se aislaron, identificaron y caracterizaron tres rizobacterias con efecto antagonico sobre este hongo. Se aislaron 656 bacterias en muestras de suelo de la rizosfera de plantas de cebolla (<em>Allium cepa</em>). Y se evaluó el antagonismo <em>in vitro</em> a <em>S. cepivorum</em>. 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Revista Mexicana de FITOPATOLOGÍA Advance online publication, 2022 surfactins), lytic enzymes (chitinases and b-1,3glucanases), siderophores (Bacillibactin), and toxins (d-endotoxins). They also have the ability to promote plant growth (Villarreal-Delgado et al, 2017;Jiménez-Delgadillo et al, 2018;Kang et al, 2019;Ocegueda-Reyes et al, 2020;Dai et al, 2021). Some studies have shown that these bacteria can induce a systemic resistance response in plants by eliciting molecules (lipopeptides, phytohormones, and volatile compounds).…”
Section: Mexican Journal Of Phytopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Revista Mexicana de FITOPATOLOGÍA Advance online publication, 2022 surfactins), lytic enzymes (chitinases and b-1,3glucanases), siderophores (Bacillibactin), and toxins (d-endotoxins). They also have the ability to promote plant growth (Villarreal-Delgado et al, 2017;Jiménez-Delgadillo et al, 2018;Kang et al, 2019;Ocegueda-Reyes et al, 2020;Dai et al, 2021). Some studies have shown that these bacteria can induce a systemic resistance response in plants by eliciting molecules (lipopeptides, phytohormones, and volatile compounds).…”
Section: Mexican Journal Of Phytopathologymentioning
confidence: 99%
“…Bacillus. Es el género bacteriano más explotado para la producción de biofungicidas debido a su versatilidad de mecanismos de control biológico, como la producción de compuestos volátiles, antibióticos (bacilomicina, iturinas, fenicinas, fengicinas, subtilinas, surfactinas), enzimas líticas (quitinasas y b-1,3-glucanasas), sideróforos (Bacillibactina), toxinas (d-endotoxinas); además de la capacidad de promoción del crecimiento vegetal (Villarreal-Delgado et al, 2017;Jiménez-Delgadillo et al, 2018;Kang et al, 2019;Ocegueda-Reyes et al, 2020;Dai et al, 2021). Algunos estudios han demostrado que estas bacterias, pueden inducir respuesta sistémica en plantas por moléculas elicitoras (lipopéptidos, fitohormonas y compuestos volátiles), y activa la síntesis de ácido salicílico, etileno, ácido jasmónico y ácido abscísico que regulan el sistema de defensa de diferentes cultivos agrícolas (Villarreal-Delgado et al, 2017;Vinod y Sabah, 2018).…”
Section: Mexican Journal Of Phytopathologyunclassified
“…Three samples of 100 µL were taken from the bacterial solution of each tube and sowed by dispersion on NFb with Congo red [34] and malic acid as a principal carbon source. Incubation conditions were continuous stirring (120 rpm) and a temperature of 30 • C [35] in Petri dishes, which were incubated for 24 h at 30 • C for CFU measurement.…”
Section: Quantification Of Bacteriamentioning
confidence: 99%
“…In spite of being a medicinal plant, garlic is attacked by various pathogenic agents that caused heavy economic losses to the crops. Among pathogenic agents particularly soil borne fungal pathogen Sclerotium cepivorum causes disease known as garlic white rot is a drastic yield reducing disease which prevalent in many Allium growing regions around the world [2][3][4][5][6]. The disease was first noticed in 1929 in Egypt [7] and then spread globally all over the world viz.…”
Section: Introductionmentioning
confidence: 99%